Description of Parents' Knowledge About First Aid for Febrile Seizures at Home for Toddlers in the Melati Room of The Hospital Abdul Wahab Sjahranie Samarinda - Rita Puspa Sari; Yoga Kurniawan; Ruminem Ruminem; Ida Ayu Kade Sri Widiastuti (Fakultas Kedokteran, 2023)
Background: Febrile seizures are a medical emergency that requires immediate help. Proper management is needed to avoid more severe defects resulting in frequent seizures. So first aid to deal with victims is immediately carried out to prevent severe injuries and complications in children. Aim : to describe the characteristics of respondents based on age, education, and level of knowledge of parents about first aid for febrile seizures at home for toddlers. Method: The design of this study used a quantitative descriptive approach with a survey technique with a total of 60 respondents. Data collection by filling out a questionnaire was carried out by parents who have children, with inclusion criteria: parents whose children are under five, hospitalized with a diagnosis of febrile seizures, cooperative, exclusion criteria for parents whose children are treated with a diagnosis of complex febrile seizures and the like. Results: the characteristics of respondents based on age obtained information that the majority of respondents were in the early adult age category, namely as many as 50 respondents (83.3%), and respondents who were in the late adult category, namely as many as ten people (16.7%), the characteristics of respondents based on the level high school/vocational high school education, namely 48 respondents (80%), junior high school education as many as ten respondents (16.7%) and the minor distribution was respondents with undergraduate education level, namely two respondents (3.3%). The description of the level of knowledge of respondents obtained from the results of parents' knowledge about first aid for febrile seizures at home in toddlers in the Melati room of Abdul Wahab Sjahranie Hospital Samarinda, which is included in the category of less knowledge level is 40 respondents (66.7%). The ideal type is 18 respondents (30 %) and good knowledge of 2 respondents (3.3%). Conclusion: based on the results of the study of 60 respondents, the results obtained about characteristics based on age and early adulthood were 50 respondents (83.3%), the majority of respondents had high school/vocational high school education, namely 48 respondents (80%). The level of knowledge of respondents about first aid for febrile seizures at home in toddlers was mainly in the less category, with 40 respondents (66.7%).